First record of a fossil selenariid bryozoan in South America - López Gappa, Juan José (2017)
Selenariidae Busk 1854 (Bryozoa) is considered endemic to Australia and New Zealand. Here we describe a new species of Selenaria Busk 1854 from the lower Miocene Monte León Formation (Patagonia, Argentina). Selenaria lyrulata sp. nov. is characterized by autozooids with a lyrula-like, anvil-shaped cryptocystal denticle, opesiular indentations and lateral condyles, as well as avicularia with a shield of fused costae. This is the first record of a selenariid bryozoan in South America.